Safety, Tolerability and Pharmacokinetics of Orally Inhaled Zanamivir: A Randomized Study Comparing Rotacap/Rotahaler and Rotadisk/Diskhaler in Healthy Adults. Issue 6 (August 2013) - Weller, Stephen; Jones, Lori S; Lou, Yu; Piscitelli, Stephen; Peppercorn, Amanda; Ng-Cashin, Judith
Background: During a pandemic, the need for available anti-influenza medications increases. There has been extensive use of the approved zanamivir Rotadisk/Diskhaler but no clinical data are available for administration by an alternative Rotacap/Rotahaler presentation. Methods: In this randomized three-way crossover study, each healthy adult received zanamivir 10 mg every 12 h for 5 days via Rotadisk/Diskhaler, via Rotacap/Rotahaler and placebo via Rotacap/Rotahaler, with a washout period between treatments. Safety assessments were conducted throughout the study and at follow-up. Serial blood samples for pharmacokinetic analysis were collected over a 12-h dose interval on day 5 of each treatment period. Pharmacokinetic parameters were compared using a mixed-effects model. Results: A total of 18 healthy adults were recruited and 17 subjects completed the study. A total of 20 adverse events (AEs) were reported (all grade 1) by nine subjects, with no AE reported ≥1 xin any treatment group. Nasal congestion, reported by one subject in the zanamivir Rotadisk/Diskhaler group, was the only drug-related AE. No serious AEs or withdrawals due to AEs occurred during the study. There were no significant changes in clinical laboratory values, vital signs or spirometry. Serum zanamivir exposures were similar after administration via Rotacap/Rotahaler and Rotadisk/Diskhaler. Both oral inhalation presentations are likely to deliver similar zanamivir concentrations to sites of influenza infection in the respiratory tract. Conclusions: The safety and pharmacokinetic results from this study support the use of the Rotacap/Rotahaler presentation, potentially allowing an increased number of zanamivir treatment courses to be supplied in the event of an influenza pandemic.